1998
DOI: 10.2486/indhealth.36.93
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration Suppresses Gastric Motility in Healthy Men.

Abstract: The influence of whole-body vibration on gastric motility was investigated by using an electrogastrography (EGG) in seven healthy men. The EGG is usually referred to as a noninvasive technique of recording gastric myoelectrical activity by means of placing electrodes on the abdominal surface. Sinusoidal vertical vibration at each of 3 different frequencies (10 Hz, 20 Hz, 40 Hz) were randomly given to the subject seated on a platform of vibrator for 5 min. The vibration magnitude was kept at a constant of 2.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…and as to whole-body vibration impediment, many investigations about the effects of the spine on a driver are made in Europe and America [1][2][3][4] . On the other hand, there are quite a few studies on the effects of a circulatory organ system, a respiratory-organs system, and a digestive organ system [5][6][7][8][9] . Until now in our country, there is no full-scale investigation for the health disorders among workers who were occupationally exposed to whole-body vibration, there are a few investigations about some of forklift workers and taxi drivers [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…and as to whole-body vibration impediment, many investigations about the effects of the spine on a driver are made in Europe and America [1][2][3][4] . On the other hand, there are quite a few studies on the effects of a circulatory organ system, a respiratory-organs system, and a digestive organ system [5][6][7][8][9] . Until now in our country, there is no full-scale investigation for the health disorders among workers who were occupationally exposed to whole-body vibration, there are a few investigations about some of forklift workers and taxi drivers [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the e!ect of short-term WBV exposure may not be so strong because normal subjects have a normal rhythm for more than 70% of the time [12]. There have been reports of a change of magnitude in the power spectrum during WBV exposure [6,7,13]. Kjellberg and WikstroK m [6] observed a biphasic phenomenon which initially increased and then gradually decreased the power spectral density at frequencies of 3 cpm due to 3 Hz WBV.…”
Section: Discussionmentioning
confidence: 99%
“…Kjellberg and WikstroK m [6] observed a biphasic phenomenon which initially increased and then gradually decreased the power spectral density at frequencies of 3 cpm due to 3 Hz WBV. Ishitake et al [7,13] have also reported that a short-time exposure to WBV can reduce the power spectral density of the normal rhythm component. Although these results imply that gastric contraction can be a!ected by WBV, there is no further information on gastric motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma das preocupações referentes aos impactos sofridos na região do quadril é o acometimento de danos nos órgãos internos, situados na região do abdômen e quadril, os quais possuem maior sensibilidade em faixas de frequência baixas de 4 a 8 Hz (Harris & Piersol, 2002;Ishitake, Kano, Miyazaki, Ando, Tsutsumi, & Matoba, 1998). Segundo Sterkowicz (1999), os ataques inesperados no judô podem provocar danos corporais principalmente durante a projeção e a queda na região posterior do sacro.…”
unclassified